2017
DOI: 10.1001/jamapediatrics.2017.2127
|View full text |Cite|
|
Sign up to set email alerts
|

Functional Outcome After Intracranial Pressure Monitoring for Children With Severe Traumatic Brain Injury

Abstract: IMPORTANCE Intracranial pressure (ICP) monitoring is a mainstay of therapy for children with traumatic brain injury (TBI), but its overall association with patient outcome is unclear.OBJECTIVE To test the hypothesis that ICP monitoring is associated with improved functional survival of children with severe TBI. DESIGN, SETTING, AND PARTICIPANTSA propensity-weighted effectiveness analysis was conducted using 2 linked national databases with data from 30 US children's hospitals from January 1, 2007, to December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 35 publications
2
56
0
Order By: Relevance
“…This also attests to the heterogeneity of the TBI population and variations in factors on the level of both the patient and the hospital that affect the use of ICP monitoring, as reported in other studies [13]. The mortality rate of 24% for the whole sTBI cohort, after excluding those who died within 24 h, is similar to the mortality in other studies of pediatric sTBI which used patient data from the National Trauma Data Bank, a large multi-institutional database similar to VPS [11, 12]. …”
Section: Discussionsupporting
confidence: 64%
“…This also attests to the heterogeneity of the TBI population and variations in factors on the level of both the patient and the hospital that affect the use of ICP monitoring, as reported in other studies [13]. The mortality rate of 24% for the whole sTBI cohort, after excluding those who died within 24 h, is similar to the mortality in other studies of pediatric sTBI which used patient data from the National Trauma Data Bank, a large multi-institutional database similar to VPS [11, 12]. …”
Section: Discussionsupporting
confidence: 64%
“…In children with moderate TBI, management often occurs without the benefit of ICP monitoring. 2,3 Historically, various initial ICP target values have been used to guide treatment, from less than 15 mm Hg, to less than 20 mm Hg, or even less than 25 mm Hg. 10 Use of cerebral perfusion pressure to guide care also requires knowledge of ICP.…”
mentioning
confidence: 99%
“…A subsequent study by Bennet et al (63) found no evidence that ICP monitoring in pediatric patients with severe TBI improved outcome. However, unlike the groups formed by Alkhoury et al (62), the initial assessment of patients in the ICP monitoring group revealed poorer Injury Severity Scores, head Abbreviated Injury Scale scores and GCS scores and a higher risk of an intracranial hemorrhage.…”
Section: The Use Of Icp Monitoringmentioning
confidence: 94%